Evaluation Of Sun Protection Factor Value Of Water, Ethyl Acetate, And N-Hexane Fractions Of Ethanolic Extract Of Crystal Guava Fruit (Psidium Guajava. L.) By UV-VIS Spectrophotometry - Farida Kumalasari; Rahmat Hidayat; Tiara Ajeng Listiyani (CV. AFDIFAL MAJU BERKAH, 2026)
Excessive exposure to ultraviolet (UV) rays can cause various skin damage, so an effective and safe sunscreen preparation is needed. Natural ingredients, especially crystal guava fruit (Psidium guajava L.), are known to contain secondary metabolite compounds such as flavonoids that have the potential as natural photoprotective agents. Crystal Guava Fruit (Psidium guajava L.) contains several secondary metabolite compounds, namely flavonoids, saponins, and terpenoids. The content of secondary metabolites plays a role as a Sun Protection Factor, because these compounds are able to absorb UV A and UV B rays well. This study aims to determine the Sun Protection Factor (SPF) value of ethyl acetate, n-Hexane, and water fractions from crystal guava fruit (Psidium guajava L.) in vitro using the UV-Vis spectrophotometry method and to determine the fraction with the best sunscreen activity. The extract was prepared by maceration using 96% ethanol solvent, then the extract was fractionated in stages using n-Hexane, ethyl acetate, and water. SPF values ​​were determined in vitro using UV-Vis spectrophotometry at a wavelength of 290-320 nm. Each fraction was prepared in several concentrations: 200, 400, 600, 800, and 1000 ppm. The study showed that all fractions had sunscreen activity with SPF values ​​that increased with increasing concentration. The ethyl acetate fraction showed the highest activity with an SPF value of 24.249 at a concentration of 1000 ppm which is included in the ultra protection category. This study shows that the water, ethyl acetate, and n-Hexane fraction of crystal guava fruit (Psidium guajava L.) have the potential as SPF because they are in the range 2-4 (minimum category).